2012
DOI: 10.1016/j.whi.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence/Abuse and Depressive Symptoms among Female Health Care Workers: Longitudinal Findings

Abstract: Intimate partner violence and abuse (IPV/A) have been shown to have a major impact on mental health functioning. This study assessed the longitudinal association between recent IPV/A and depressive symptoms in order to identify potential targets for preventive interventions for women. Random effects models were used to examine four waves of data collected at 6-month intervals from a cohort of 1438 female healthcare workers. Recent IPV/A (e.g., sexual and physical violence, psychological abuse) in the past 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Three studies from the US [13],[26],[27] included adolescents and focused on dating violence; all of the other studies focused on IPV in adults. Four studies sampled participants from secondary schools [13],[22],[26],[27], four studies were individual or household surveys of the general population [20],[21],[23],[28], one was conducted at a college [29], one was conducted among hospital employees [30], and three sampled from a variety of venues [25],[31],[32]. The three remaining studies recruited pregnant women, two from hospitals [33],[34] and one from households in the general population [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies from the US [13],[26],[27] included adolescents and focused on dating violence; all of the other studies focused on IPV in adults. Four studies sampled participants from secondary schools [13],[22],[26],[27], four studies were individual or household surveys of the general population [20],[21],[23],[28], one was conducted at a college [29], one was conducted among hospital employees [30], and three sampled from a variety of venues [25],[31],[32]. The three remaining studies recruited pregnant women, two from hospitals [33],[34] and one from households in the general population [24].…”
Section: Resultsmentioning
confidence: 99%
“…Median attrition rate was 22.5% (interquartile range 17%–28.6%) (range 4.5% [31] to 57.1% [34]). Ten studies made use of two waves of data collection, two had three waves [23],[34], two had four waves [26],[30], one had five waves [33], and one had 14 [31]. The majority of studies included only female participants; the four studies that recruited from secondary schools also included males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Domestic Violence Prevention Act in Taiwan, the definition of IPV refers to physical, psychological, or sexual violence. IPV has a negative impact on the mental and physical health of IPV survivors, as well as adverse societal influences and detrimental effects on the survivors' families and communities [6]; Glass et al, 2010; [7] Q2 . A British survey investigating the prevalence of domestic violence found that 23.5% of women aged more than 16 years have experienced domestic violence [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hathaway et al (2000) found women who had experienced domestic abuse from their partner in the past year were more than three times as likely as women who reported no domestic abuse to have developed depression. Importantly, in a large sample study of female workers, La Flair, Bradshaw, and Campbell (2012) found that abused females (e.g., experienced abuse from a partner), when compared with nonabused females, reported greater depressive experiences over an 18-month period, independent of initial depression. This finding suggests that domestic abuse may be an important causal determinant of later depressive experiences in females.…”
mentioning
confidence: 96%